Long and winding road?: Barriers and supporting factors as perceived by entrepreneurs with disabilities. Issue 1 (31st May 2019) - Csillag, Sara; Gyori, Zsuzsanna; Svastics, Carmen
Abstract : Purpose: The purpose of this paper is to explore and analyse the barriers entrepreneurs with disabilities (EWD) face when establishing their own enterprises, as well as the supporting factors in starting and running a business. Design/methodology/approach: This is an explorative study. Data were collected using semi-structured interviews with ten Hungarian entrepreneurs with physical disabilities or sight-loss, during the summer of 2018. Findings: The paper classifies the barriers and supporting factors, as personal, economic and social. Based on the perceptions of the entrepreneurs, personal characteristics, identity and various types of family support play an important role in becoming entrepreneurs, but the entrepreneurial ecosystem generally is not favourable in Hungary, and there are no special support programmes focussing on EWD. Research limitations/implications: Sample size is a serious limitation: the ten entrepreneurs do not represent in any sense the entire EWD community in Hungary, so the patterns found cannot be considered a generally valid picture. Originality/value: The article contributes to the literature on entrepreneurship and disabilities, especially through the systematic review of the possible barriers and supporting factors and to the existing empirical body of knowledge by shedding light on the barriers and supporting factors in a rarely investigated region, in Central Europe: Hungary.